Influence of microplastics on the structure and function of deep-sea communities during long-term enrichment processes - Lv, Shiwei; Li, YuFei; Yuan, Qing; Lu, Yao; Ye, Yonglian; Zhong, Yangsheng; Liu, Renjiu; Zhao, Sufang; Xia, Jingyu; Zeng, Lingyu; Shao, Zongze (Frontiers in Marine Science, 2024)
Microplastics are widespread pollutants in aquatic environments, posing a significant threat to the health of marine ecosystems. However, little is known about the impact of plastics on deep-sea microbial communities. In this paper, we investigated the effects of polystyrene (PS) microplastics with three particle sizes (60 nm, 600 nm and 1 µm) and three concentrations (10, 50, 150 mg/L) as well as PS films (1 × 1 cm) on the deep-sea microbial community inoculated with water of 3370 m water depth from Pacific Ocean. Microplastics surface rotting (600 nm and 1 µm) and further fragmentation (60 nm) were observed caused by plastic-degrading microbial erosion after 50 days' incubation. Similarly, deformation of PS film, including formation of obvious wrinkles and deep pits and the generation of microplastics and nanoplastics were also observed. Microplastics from commercial and plastic films could stimulate the bacterial community to secrete extracellular polymeric substance (EPS), favouring biofilm formation and resistance to external stress. Compared with larger microplastics, 60 nm microplastics and plastic films significantly inhibited the growth of bacterial communities with enhanced reactive oxygen species (ROS) production. The abundance of Moraxellaceae dominated in all enriched samples with the addition of microplastics, while the abundance of Alcanivoracaceae also increased in the 60 nm and plastic film enrichments, in contrast to dominant bacteria of Colwelliaceae, Marinobacteraceae, Rhodobacteraceae and Alcanivoracaceae the deep seawater in situ. Correspondingly, the functional changes of the communities were observed via functional prediction by 16S rRNA gene based on their alterations in bacterial community structure. The study provides insights into the effects of microplastics and nanoplastics on deep-sea microbial communities.